GATA-3 expression and its correlation with prognostic factors and survival in canine mammary tumors - Diniz-Gonçalves, Gabriel Saraiva; Hielm-Björkman, Anna; da Silva, Vanessa Bonfim; Ribeiro, Lorena Gabriela Rocha; da Costa Vieira-Filho, Carlos Humberto; Silva, Laís Pereira; Barrouin-Melo, Stella Maria; Cassali, Geovanni Dantas; Damasceno, Karine Araújo; Estrela-Lima, Alessandra (Frontiers in Veterinary Science, 2023)
The transcription factor GATA-3 plays a significant role in mammary gland development and differentiation. Recent studies on human oncology have demonstrated its association with favorable pathologic factors in breast cancer. Canine mammary tumors, proposed as comparative and translational study models, have epidemiological, clinical, biological, and genetic characteristics similar to those of human breast cancers. Here, we evaluated the frequency of GATA-3 expression in mammary tumors of dogs and its relationship with prognostic factors and survival. Tumor samples were obtained from 40 female dogs and grouped according to histological type into benign tumors (n=10), carcinoma in mixed tumors (CMTs) (n=20), and aggressive tumors (n=10). CMTs were further separated according to histological grade, and data on clinical staging and diagnosis, histopathological grading, and survival rate were collected. GATA-3 and estrogen receptor (ER) expression were higher in benign and well-differentiated carcinomas than in aggressive tumors, which showed greater Ki-67 expression. The expression rate of ER in the studied groups was equivalent to that of GATA-3. We identified a strong positive correlation between GATA-3 and ER expression frequencies and a negative correlation between those of GATA-3 and Ki-67. There were associations between GATA-3 (p<0.001), Ki-67 (p=0.003), tumor size (p<0.001), clinical stage (p=0.002), lymph node metastasis (p<0.001) and histological grade (p<0.001) by univariate survival analysis. The parameters ER (p=0.015) and GATA-3 (p=0.005) also influenced survival in a multifactorial manner. Kaplan-Meier analysis of survival curves validated our previous findings that dogs with GATA-3 expression in ≥ 79.4% of cells had significantly higher survival rates (p<0.001). The performance analysis showed that the expression of GATA-3 in ≥ 79.4% of cells effectively predicted survival or death in dogs with mammary tumors. Collectively, these results suggest that GATA-3 can be a relevant marker in the study of mammary tumor progression and has potential as a prognosis marker for predicting outcomes in canine mammary tumors.